Youth mental health: how same-sex attraction, peer victimization, future beliefs, and personal competence relate to internalizing problems - Gabriël van Beusekom; Kate L. Collier; Mark Assink; Henny M.W. Bos (International Journal of Adolescence and Youth, 2025)
A cross-sectional survey was conducted with 949 Dutch adolescents aged 15 to 18 to examine whether peer victimization, future beliefs, and personal competence mediate the relationship between sexual orientation and internalizing problems. Additionally, the study explored whether sex assigned at birth moderates these mediation effects. Serial mediation was found through peer victimization and future beliefs, and through peer victimization and personal competence, but only for male-assigned adolescents. Male-assigned adolescents with same-sex attraction (SSA) reported more peer victimization, which related to more negative future beliefs and less personal competence, which both were associated with more internalizing problems. For all adolescents, future beliefs also independently mediated the SSA – internalizing problems relationship. SSA was directly related to more negative future beliefs, which in turn related to more internalizing problems, regardless of peer victimization. These findings stress the need to address peer victimization and promote psychological resources to improve mental health in sexually diverse youth.